The Effectiveness of Qiro’ah and Ummi Methods in Enhancing Qur'an Reading Skills - Rahman, Abd.; Al Jauhari, Shofwan; Taslim, Muhammad (LP. Ma'arif Janggan Magetan, 2024)
This study aims to compare the effectiveness of the Qiro’ah and Ummi methods in enhancing Qur'an reading skills in Jayapura. This research uses a qualitative design with data collected through observation, interviews, and documentation. The study subjects were Madrasah Ibtidaiyah Unggulan Darul Qur’an Wadda’wah Argapura and SDIT Permata Hati As-Salaam students. Data analysis was conducted descriptively and qualitatively by systematically organizing, reducing, presenting, and concluding the data. The results show that the Qiro’ah and Ummi methods effectively improve Qur'an reading skills. The Qiro’ah method focuses on mastering makharijul huruf and tajweed through pictorial media, while the Ummi method emphasizes a motherly approach with direct learning and repetition. Both methods successfully improved students' Qur'an reading fluency. The implications of this research indicate that both methods can be applied in various Islamic educational institutions in Jayapura to improve students' Qur'an reading skills. Further research is needed to explore other factors that influence the effectiveness of Qur'an learning.